Aspectos emocionales y éticos de la adecuación del esfuerzo terapéutico: Revisión bibliográfica - Naranjo Peña, Valeria de los Ángeles (2023)
ABSTRAC The adequacy of therapeutic effort (AET) is a clinical decision to stop diagnostic and/or treatment activities for patients with terminal illnesses or at the end of life, in order to ensure that the transition between life and death is adequate and humane. . The present study was developed through a bibliographic review with the aim of systematizing emotional and ethical aspects of AET. The search was carried out in the Web of Science and Medline databases, in the ProQuest platform and in the SciELO digital library. The population, intervention, comparison, and results and objectives (PICO) format was used to establish the research question and define the descriptors, the methodological quality was evaluated by applying the Critical Appraisal Skills Program Spanish (CASPe) guide. Nineteen scientific articles were selected, which allowed the identification of the following results: among the attitudes and emotions expressed about the AET were fear, sadness, fear, confusion, and dissatisfaction. Decisions are based on the Code of Medical Ethics, on the patient's clinic and on bioethical principles. Nursing professionals experience difficulties by not being taken into account to decide their application, work stress, lack of records in medical records, lack of supplies and protocols, and obstacles in communication with family members. Keywords: Nursing, Quality of life, Palliative care, End of life, Right to die